2022
DOI: 10.31083/j.fbl2701031
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific and cell/tissue-dependent effects of p38 MAPKs in regulating inflammation and inflammation-associated oncogenesis

Abstract: p38 MAPK (mitogen-activated protein kinases) family proteins (α, β , γ and δ ) are key inflammatory kinases and play an important role in relaying and processing intrinsic and extrinsic signals in response to inflammation, stress, and oncogene to regulate cell growth, cell death and cell transformation. Recent studies in genetic mouse models revealed that p38α in epithelial cells mostly suppresses whereas in immune cells it promotes inflammation and inflammation-associated oncogenesis. On the contrary, p38γ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
(152 reference statements)
1
7
0
Order By: Relevance
“…Although p38γ MAPK has been less investigated, it has unique functions particularly in the regulation of cell cycle progression, mobility, migration/invasion, cancer stem cells (CSCs), and epithelial-mesenchymal transition (EMT) ( 10 , 11 ). The activation and over-expression of p38γ MAPK is associated with malignant tumors ( 11 , 12 ). We have previously showed that alcohol activated p38γ MAPK, which may lead to increased CSCs and metastasis of breast cancer cells ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although p38γ MAPK has been less investigated, it has unique functions particularly in the regulation of cell cycle progression, mobility, migration/invasion, cancer stem cells (CSCs), and epithelial-mesenchymal transition (EMT) ( 10 , 11 ). The activation and over-expression of p38γ MAPK is associated with malignant tumors ( 11 , 12 ). We have previously showed that alcohol activated p38γ MAPK, which may lead to increased CSCs and metastasis of breast cancer cells ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Moreover, the mitogen‐activated protein kinase (MAPK) cascade, as a conserved signaling module downstream of receptors/sensors, has been implicated as playing a critical regulatory function in the generation of proinflammatory cytokine. [ 17 ] Extracellular regulated protein kinase (ERK), c‐Jun N‐terminal kinase (JNK), and p38 mitogen‐activated protein kinase (p38) are the major kinases in the MAPK signaling pathway. Activation of the MAPK/ERK/JNK/P38 pathway is accompanied by the activation of inflammatory signaling pathways, such as nuclear factor kappa‐B (NF‐κB) and B‐cell lymphoma‐2 (Bcl‐2), which mediate the expression of inducible nitric oxide synthase (iNOS), IL‐1β, tumor necrosis factor‐α (TNF‐α), and other markers of inflammation, further exacerbating the development of UC.…”
Section: Introductionmentioning
confidence: 99%
“…Although these isoform-specific activations are important for different cellular outcomes, the mechanisms involved are largely unknown [ 2 , 5 , 6 ]. Isoform-specific and tissue-dependent effects of p38 MAPKs in inflammation and inflammation-associated oncogenesis have been recently reviewed [ 7 ]. This manuscript will focus on recent discoveries regarding p38γ inflammatory and metabolic signaling in physiology and diseases.…”
Section: Introductionmentioning
confidence: 99%